An improved analysis of the N2O absorption spectrum in the 1.18 µm window. (February 2022) - Karlovets, E.V.; Tashkun, S.A.; Kassi, S.; Campargue, A.
Highlights: High sensitivity CRDS of nitrous oxide at 10 Torr near 1.18 µm. Small self-induced pressure shifts are measured at 10 Torr and compared to empirically determined values. About 4000 lines of 69 bands of five isotopologues are measured. Band-by-band spectroscopic parameters derived for 69 bands. Six local resonance interactions are analysed and some extra lines are identified. Abstract: A high-sensitivity absorption spectrum of natural nitrous oxide has been recorded at 10 Torr between 8321 and 8620 cm −1 (1.20 – 1.16 µm). The used cavity ring down spectrometer was referenced to a self-referenced frequency comb providing an accurate frequency scale of the spectra. The predictions of effective operator models were used for the line assignment. All identified bands correspond to the Δ P =14–16 series of transitions, where P  = 2 V 1 + V 2 +4 V 3 is the polyad number ( Vi=1–3 are the vibrational quantum numbers). A total number of 3975 transitions belonging to the 14 N2 16 O, 14 N 15 N 16 O, 15 N 14 N 16 O, 14 N2 18 O, and 15 N2 16 O isotopologues were measured with estimated accuracy better 1 × 10 −3 cm −1 for most of the lines. Compared to the recent analysis of N2 O spectra at 1 Torr recorded in the same region (Karlovets et al. JQSRT, 262 (2021) 107, 508, doi: 10.1016/j.jqsrt.2021.107508), the higher pressure of the recordings and improved quality of the predictions have allowed to: (i) newly assign twenty-two bands, including the 4 ν 3 band of the 15 N2 16 O minor isotopologue, ( ii ) extend the assignments of previously known bands, ( iii ) determine the small self-induced pressure shifts of the two strongest bands (less than 10 −4 cm −1 ) by difference of the line positions at 1 and 10 Torr and use them to obtain the zero-pressure value of the line positions, ( iv ) derive new or improved spectroscopic constants of 69 bands from the standard band-by-band analysis, and ( v ) analyze six local resonance perturbations affecting three bands, including the identification of a few extra lines due to intensity transfer. Finally, the comparison of the line positions and intensities with their predicted values and with available databases is discussed. Graphical abstract: Image, graphical abstract